Calling my name - Tamani, Liara (Greenwillow Books, an imprint of HarperCollinsPublishers, 2017)
Calling My Name is a striking, luminous, and literary exploration of family, spirituality, and self - ideal for readers of Jacqueline Woodson, Jandy Nelson, Naomi Shihab Nye, and Sandra Cisneros. This unforgettable novel tells a universal coming-of-age story about Taja Brown, a young African American girl growing up in Houston, Texas, and deftly and beautifully explores the universal struggles of growing up, battling family expectations, discovering a sense of self, and finding a unique voice and purpose. Told in fifty-three short, episodic, moving, and iridescent chapters, Calling My Name follows Taja on her journey from middle school to high school. Literary and noteworthy, this is a beauty of a novel that captures the multifaceted struggle of finding where you belong and why you matter. --